Methotrexate and doxycycline interaction: a rare cause of pancytopenia. Issue 5 (31st May 2019) - Arslan, Ahmad; Zain, Muhammad Abdullah; Mukhtar, Maryam; Ullah, Waqas; Roomi, Sohaib
Abstract : Methotrexate (MTX) was originally formulated as one of the first antitumour drugs due to its ability to alter folate metabolism, which renders it to be an antiproliferative agent. Classically, the higher dosage is administered via parenteral route, in a cyclical fashion, to achieve antitumour effects. Patients on high doses of MTX are prone to develop rare complications of myelosuppression and pancytopenia, in a dose-dependent fashion, secondary to altered folate metabolism. 1 Herein, we present a unique case of rheumatoid arthritis presented with pancytopenia due to low-dose MTX and doxycycline drug interaction. We also report the successful management of pancytopenia and oral ulcers with combination therapy of leucovorin and granulocyte colony-stimulating factor.